Elementary School Learning Transformation: Using Game-Based Media to Enhance Student Activities Interactively - Rambe, Andina; Humaidah Fatimah Parapat; Rilwan Hadinata; Hasratuddin (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
This research aims to analyze the transformation of learning in primary schools (SD) using game-based media to enhance student activities interactively. Game-based media is applied to a variety of subjects with stages designed to facilitate 21st century skills. This research uses qualitative methods to identify the impact, benefits in reducing student anxiety and boredom, and constraints in implementation. Results show that game-based media can increase student engagement interactively. Game-based media can be used in various subjects, providing a more enjoyable learning experience, facilitating better interaction, offering more interesting and dynamic learning for students, reducing anxiety and boredom, and facilitating 21st century skills, named by Critical thinking, Creativity, Collaboration, Communication. Despite the challenges of limited infrastructure and teacher training, the potential of gaming media is huge in creating a more effective learning experience. Further development is expected to overcome these obstacles by strengthening technological support and pedagogical training for teachers.